NUTRITIONAL SUPPORT: BASIC PRINCIPLES OF ENTERAL NUTRITION - LEANDRO, Vânia Aparecida (1990)
The nutritional support has a crescent importance as therapeutic and coadjuvant method in several clinical and surgical conditions. The present article emphasizes the concepts used in enteric nutritional support, clinical indications, alternative ways of administration, sorts of diets, classifications and characterístics, complications and control of nutrition by tubes. Contribute in a satisfatory manner to encourage the useful knowledge in nutritional support area, contributing thus, the decrease of morbidity and mortality in patients, when pathological and clinícal situations would indicate a less optimistic prognostic.